Sampling based path planning algorithm for UAV collision avoidance - Saravanakumar, A; Kaviyarasu, A; Ashly Jasmine, R (Sadhana (Bangalore), 2021)
Path planning of Unmanned Aerial Vehicles (UAVs) avoiding collisions with moving obstacles or other UAVs in motion, is one of the key functions to fulfill their mission. The current work is focused on the development of sampling-based path planning methods for UAV. Under this method, standard Rapidly exploring Random Tree algorithm (RRT) is chosen, but RRT algorithm faces some limitations. Thus few developments were made in RRT by simplifying the node connection strategy, to generate feasible path satisfying the operating environment constraints dictated. Simplified node connecting strategy as Modified RRT (MRRT) and collision avoidance using reachable sets is developed to avoid collisions along the path. It is demonstrated in the python window using Python software. The proposed algorithm can develop a path in a short time duration and guides the vehicle to bypass the obstacles to avoid collision.